Segmentacja internautów z wykorzystaniem danych symbolicznych i metod klasyfikacji - Wilk, Justyna (Market Segmentation of Internet Users Based on Symbolic Data and Cluster Analysis, 2009)
The aim of the paper is to suggest market segmentation procedure based on symbolic data and cluster analysis. The first part of the paper focuses on symbolic data and their sources in market segmentation research. Furthermore, the taxonomy of symbolic data clustering methods was presented. In the second part, the results of market segmentation of Internet users based on symbolic data from questionnaire survey were discussed. The hybrid approach was used to classify Internet users. First of all the consumers were divided into non-buyers and buyers via Internet. A special attention was paid to the second ones. The clustering procedure of symbolic objects was suggested. In the classification results, three segments of buyers via Internet were revealed: "Discoverers", "Agents", "Sceptics". (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 47, s. 315-323